The Students’ Errors in Speech Production on Interpersonal Speaking Class - Nurhayati Sitorus (Jurnal Studi Guru dan Pembelajaran, 2021)
The research aims to investigate the students’ errors in speech production, to know the types of errors and the dominant errors that the first semester English Department students did in interpersonal speaking class. The research method used in this research was descriptive qualitative research. The subject of the research was the first semester English Department students. They were 30 students. They were selected randomly. The data was collected through observation and tape recorder. The instrument of the research was oral test. The data was analyzed by using Clark and Clark theory. The result of the research shows that there are six students’ errors in speech production. They are silent pause (54,15%), filled paused (9,74%), repetition (32,95%), unretraced (0,29%), correction (1,72%) and slip on the tongue (1,15%). The dominant errors in speech production is silent pause. The source of errors are cognitive reason, social reason, and psychological or affective reason. Besides that, students’ errors are also found in linguistic competence such as grammatical and pronunciation. And the causes of errors in linguistic competence are first language (mother language), translation, carelessness and language transfer.